Predicted antiviral potential of phytochemicals prolific in Cleistanthus bracteosus Jabl. and essential oils of Artemisia scoparia and Thuja orientalis against Nipah virus and Human metapneumovirus: An AI-driven in-silico study - Mackingsley Kushan Dassanayake; Teng-Jin Khoo; Chien Hwa Chong; Mohammed Tahir Ansari; Patrick Di Martino; Fernando Berton Zanchi; Adam Figiel; Antoni Szumny; Omar Ashraf Elfar; Christophe Wiart; Rachael Symonds (PLoS ONE, 2026)
The recent Nipah virus (NiV) epidemic and human metapneumovirus (hMPV) outbreak have had a significant impact on human health and society worldwide. The attachment glycoprotein (G) and fusion glycoprotein (F0) of NiV and hMPV are essential for pathogenesis and are potentially pronounced targets for antiviral treatment. In the present study, we utilised computational methods to analyse the predictive antiviral potential of phytochemicals present in Cleistanthus bracteosus and in the essential oils of Artemisia scoparia and Thuja orientalis against NiV and hMPV. Molecular docking and dynamics simulations were the primary tools for assessing the binding interactions of compounds detected by GC-MS. Three out of four compounds tested (digoxigenin, cedrene and cedrol) exhibited remarkable binding affinities between −7.7 kcal/mol and −6.2 kcal/mol for NiV fusion glycoprotein (F0), and between −8.3 kcal/mol and −7.1 kcal/mol for NiV attachment glycoprotein (G). Similarly for hMPV fusion glycoprotein (F0), the aforesaid compounds showed binding affinities between −8.1 kcal/mol and −6.4 kcal/mol. Moreover, MD simulations illustrated phytochemical interacting amino acid residues associated with each receptor of NiV and hMPV. These phytochemical compounds were further evaluated using ADMET platforms. In conclusion, the present in silico work predicts for the first time the predicted potential of using major compounds present C. bracteosus , A. scoparia and T. orientalis as a novel anti-viral therapeutic strategy to control the entry and pathogenesis of NiV and hMPV. Despite few RMSD fluctuations in protein-ligand complexes stemming from structural alterations in the beta-turn-beta and helix-coil-helix, the simulations remain mostly stable from 50 ns till 100 ns.